2016
DOI: 10.1590/1679-395146821
|View full text |Cite
|
Sign up to set email alerts
|

Eu, Alex, da etnia Guarani: o testemunho de um estudante indígena de administração e seu duplo pertencimento

Abstract: Resumo A presença de indígenas nas universidades públicas brasileiras é um fenômeno recente, datado de 2002, com a inédita experiência de ingresso e permanência desses sujeitos nas universidades do Paraná. A trajetória dos estudantes de diferentes cursos de graduação reflete a existência de um duplo pertencimento: ser indígena e ser acadêmico simultaneamente. Este estudo apresenta o testemunho como estratégia do método de história de vida, fazendo uso do diálogo testemunhal e tendo como um dos autores um estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…Raoni and Ubirajara cite the need for knowledge about public administration and project management as skills learned in the course that can be used in indigenous lands. All of this resumes what was presented by Bajada and Trayler (2014) and Cassandre, Amaral and Silva (2016) regarding the importance of the emergence of the profession of administrator in indigenous lands. However, as well as in communities and non-indigenous groups, it has been reported that, in indigenous lands, there are internal conflicts and factionalisms between family groups that can impede the performance of these new professionals or reduce the use of this knowledge.…”
Section: Trajectories and Expectations About The World Of Worksupporting
confidence: 57%
See 1 more Smart Citation
“…Raoni and Ubirajara cite the need for knowledge about public administration and project management as skills learned in the course that can be used in indigenous lands. All of this resumes what was presented by Bajada and Trayler (2014) and Cassandre, Amaral and Silva (2016) regarding the importance of the emergence of the profession of administrator in indigenous lands. However, as well as in communities and non-indigenous groups, it has been reported that, in indigenous lands, there are internal conflicts and factionalisms between family groups that can impede the performance of these new professionals or reduce the use of this knowledge.…”
Section: Trajectories and Expectations About The World Of Worksupporting
confidence: 57%
“…The research by Amaral (2010) and other authors (NOVAK, 2007;PAULINO, 2008;CASSANDRE, AMARAL and SILVA, 2016;ANGNES, FREITAS, KLOZOVSKI et al, 2017;AMARAL, FRAGA and RODRIGUES, 2016) demonstrated how complex the indigenous educational path within universities can be. The reflections of Bajada and Trayler (2014) include the training of administrators as an emergency for the experience of indigenous peoples, as also presented in the study by Cassandre, Amaral and Silva (2016). It is necessary to highlight here that, based on the indemnification processes of hydroelectric and railroad undertakings, among others, the indigenous communities start to develop their own productive projects, requiring trained people to manage these businesses that belong to their communities.…”
Section: Methodological Pathmentioning
confidence: 97%
“…In this sense, it was possible to verify that the emergence of indigenous people in universities is complex. The research by Amaral (2010) and other authors (NOVAK, 2007;PAULINO, 2008;CASSANDRE, AMARAL and SILVA, 2016;ANGNES, FREITAS, KLOZOVSKI et al, 2017;AMARAL, FRAGA and RODRIGUES, 2016) demonstrated how complex the indigenous educational path within universities can be. The reflections of Bajada and Trayler (2014) include the training of administrators as an emergency for the experience of indigenous peoples, as also presented in the study by Cassandre, Amaral and Silva (2016).…”
Section: Methodological Pathmentioning
confidence: 97%
“…In the international database, ProQuest, 23 articles were found from eight different countries, of which 12 are related to indigenous higher education and another six are related to intercultural education. Thus, it was found that there are few studies related to indigenous higher education (in these databases), as indicated by studies by some authors about the topic (AMARAL, 2010;AMARAL, RODRIGUES and BILAR, 2014;CASSANDRE, AMARAL and SILVA, 2016;ANGNES, FREITAS, KLOZOVSKI et al, 2017;AMARAL, FRAGA and RODRIGUES, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…In a brief literature review on the policies of affirmative action with indigenous peoples in higher education, we found out that most of most of them are in areas of sociology and anthropology, with little contribution to psychology (Oliveira, Maia, & Lima, 2020), which indicates the relevance of our article to our area. Among the obtained texts, the ones that contained the indigenous people's discourses as sources of information, we were able to verify that permanence is a crucial point for these groups: they face prejudice, discrimination, disrespect to indigenous cultures, lack of specific policies for indigenous peoples, and consequently many drop out (Beltrão & Cunha, 2011;Bergamaschi et al, 2018;Cassandre, Amaral, & Silva, 2016;Calegare et al, 2017;David et al, 2013).…”
Section: Introductionmentioning
confidence: 94%